The effectiveness of budget benchmarks on the financial performance of local authorities, a case study of the Rural and Urban Local Authorities in Zimbabwe.)‖. - Chauke, Jackson (2020)
This study investigated the effectiveness of budget benchmarks on the financial performance of local authorities, a case study of the Rural and Urban Local authorities in Zimbabwe. A hypothesis was developed to look at the relationship between budget benchmarking and financial performance. A descriptive research design was used in this research. The population of the study was 97 consisting of Directorate and senior officials from the Ministry of Local Government, Public Works and National Housing and council senior staff. The study used primary data collected through a questionnaire send through emails, interviews to the Directorate and secondary data analysed from local authorities budgets and local authorities Service Level Benchmarking report from the period 2013 to 2017. The data was analysed by the use of descriptive statistics which included inferential statistics such as regression and bivariate correlation. Results show that benchmarking has an influence in the financial performance of local Authorities through satisfaction by residents who pay bills and enjoy the services they require. The changing and dynamism of the Local government sector needs actors to be proactive as residents need quality services which correlates with value for money, this came out from the study. The theoretical outline and findings of this research will urge scholars to further scrutinise on other strategic best practices of the sector regarding the execution and implementation of processes which eases service provision and define best ways to utilise available resources economically but not compromising service provision.